ANALYSIS OF OVARIAN CYST LAPAROSCOPIC SURGERY AMONG SECOND TRIMESTER PREGNANT WOMEN AT NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY FROM 2021 TO 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed at analysis of laparoscopic surgery of ovarian cyst among 2 trimester pregnant women at National hospital of Obstetrics and Gynecology from 2021 to 2023.Subjects and methodology: All women in the second trimester of pregnancy diagnosed and treated for ovarian tumors by laparoscopic surgery at the National Hospital of Obstetrics and Gynecology from January 1, 2021 to December 31, 2023.Results: The age group from 25-29 accounts for 40.8%. The average size of the tumor was 9.6±4.4 cm. Of these, tumors measuring 6-10cm account for the largest proportion (75.7%). The majority had planned surgery (93.2%). Tumor removal surgery accounts for a large proportion of 88.4%, tumor resection accounts for 11.6%. Ovarian cysts in pregnancy in this study were dominated by ovarian dermoid tumors with 65.0%. After surgery, only 01 patient had bleeding (1.0%) and then had a miscarriage. The average hospital stay was 4.8±0.5 days.Conclusion: Laparoscopic ovarian tumor surgery in the second trimester was a effective method with low risk of complications. However, highly skilled surgeons are required to minimize the risk for mother and fetus.
Keywords: Laparoscopy, ovarian cyst, second trimester, national hospital of obstetrics and gynecology